Interbody fusion usе after discectomy in the thoracic spine - Slinko, E. I.; Zolotoverkh, A. M.; Ermolyev, A. I. (Ukrainian Neurosurgical Journal, 2009)
During the period from 1999 to 2009 at 16 patients, have been operated because of thoracic spine hernia, the interbody fusion was used. For patient’s functional status estimation a scale for patient with thoracic spine hernia status estimation (QTMR) was used. In the early postoperative period pain intensity decreased or pain has disappeared at 12 patients, motor disorders — at 15, conducting sensitiveness was improved — at 16, improvement of pelvic organs function was observed at 4 patients, reduction of segmental and radicular disorders — at 10, 8 patients could walk without assistance in the early postoperative period.